Criminal Sanctions For B3 Waste Management in Hospitals or Health Facilities - Deny Suprayoga (Jurnal Indonesia Sosial Teknologi, 2024)
As a health service facility, the hospital is a gathering place for sick and healthy people, can be a place for disease transmission and allows environmental pollution and health problems. Today's management of the hospital environment is no longer a consumptive partial part but is a series of cycles and management strategies for homes. Hospitals need to develop hospital environmental management capacity to provide direct and indirect benefits to improve the quality of hospital services. Hospital environmental management has complex problems. One of them is the problem of hospital waste, which is very sensitive to government regulations. Hospitals, as one of the largest waste generators, have the potential to cause pollution to the surrounding environment, which will harm the community and even the hospital itself. Hospital environmental management is no longer a consumptive partial part but a series of hospital management cycles and strategies to develop hospital environmental management capacity to provide direct and indirect benefits to improving the quality of hospital services. Hospital environmental management has complex problems. One of them is the problem of hospital waste, which is very sensitive to government regulations. Hospitals, as one of the largest waste generators, have the potential to cause pollution to the surrounding environment, which will harm the community and even the hospital itself.